PENDAMPINGAN EKTRAKURIKULER KIR MELALUI PENGGUNAAN ASESMEN AUTENTIK BERBASIS MINI-RISET - Ina Setiawati Setiawati; Rahma Widiantie; Handayani Handayani (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
Education in the modern era demands the development of student competencies beyond the core subjects. One of the efforts to achieve this is extracurricular, especially the Adolescent scientific group (KIR). KIR provides students with opportunities to develop their research, problem-solving, and creativity skills. To maximize the benefits of this activity, effective KIR assistance is needed and the use of mini-research-based authentic assessments can help facilitate KIR assistance in achieving its goals. The KIR Assistance Method includes the stages of planning, implementation, and evaluation. The results of KIR's mentoring activities include helping to facilitate students to add insight academically and scientific paper writing skills, 60% of students have been able to make mini-research designs well, but 80% of students stated that students still experience problems in terms of time to do the mini research.